TRAINING UNIVERSITY TEACHERS TO DELIVER NON-LINGUISTIC EDUCATIONAL COURSES IN ENGLISH - Evgeniya O. Frantcuzskaia; Valentina N. Deryusheva (Moscow Polytechnic University, 2016)
The article considers the problem of how university teacher commitment to deliver educational courses in English matches the modern quality requirements of training future specialists. The authors analyze the system of university advanced teacher training programmes focused on developing educational courses in English. The system contains three programmes, which provide a technical university content teacher with a sufficient didactic toolkit to design and deliver non-linguistic educational courses in English. The paper also presents the viewpoint on designing a blended educational course in English for international students. The course focused on problem-based teaching and learning has demonstrated its high efficiency in developing student motivation, their critical thinking skills and total class participation. Thus, advanced training programmes described promote both academic staff didactic competence and the quality of future engineer training.